2021
DOI: 10.1101/2021.02.24.432666
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cryo-EM study on the homo-oligomeric ring formation of yeast TRiC/CCT subunits reveals TRiC ring assembly mechanism

Abstract: The complex eukaryotic chaperonin TRiC/CCT helps maintain cellular protein homeostasis, however, its assembly mechanism remains largely unknown. To address the subunit specificity in TRiC assembly, we express each of the individual yeast TRiC subunit in E. coli. Our cryo-EM structural study and biochemical analyses demonstrate that CCT1/2/6 can form TRiC-like homo-oligomeric double ring (HR) complex, however ATP-hydrolysis cannot trigger their ring closure; after deletion of the long N-terminal extension, CCT5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 67 publications
(101 reference statements)
2
5
0
Order By: Relevance
“…4a-c). Consistently, previous studies also suggested important roles of CCT3/6/8 in the recognition of other substrates such as mLST8, reovirus σ3 capsid protein, and AML1-175 [26][27][28] . Taken together, the .…”
Section: Asymmetric Working Mechanism Of Tricsupporting
confidence: 85%
See 1 more Smart Citation
“…4a-c). Consistently, previous studies also suggested important roles of CCT3/6/8 in the recognition of other substrates such as mLST8, reovirus σ3 capsid protein, and AML1-175 [26][27][28] . Taken together, the .…”
Section: Asymmetric Working Mechanism Of Tricsupporting
confidence: 85%
“…TRiC-mediated substrate folding is closely related to its ATP-driven conformational cycle [22][23][24][25] . TRiC has been proved to display subunit specificity in the complex assembly, ATP consumption and ring closure 16,19,26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, it has been found that, differently from other subunits, CCT5 (and in a less competent manner also the CCT4 subunit) has the ability to form homo-oligomeric complexes (micro-complex and single ring), supporting the hypothesis that single CCT5 homo-oligomeric rings may be the base assembly units for the formation of the functional hetero-oligomeric CCT hexadecamer ( Sergeeva et al, 2019 ; Liu et al, 2021 ). A certain functional ability of the mutant CCT5 in our patient is suggested by its ability to form part of the CCT team, i.e., the CCT hexadecamer.…”
Section: Discussionmentioning
confidence: 88%
“…In many paralogs that interface was likely only partly lost as their specific positions in the ring were entrenched, as has been demonstrated for other multimeric complexes with ring topologies 55,56 . Our results could be explained if the residual affinity between paralogs that are not adjacent in TRiC reflects incomplete loss of ancient contacts 7,17,[47][48][49] . Whether they signify moonlighting functions or byproducts of evolution, non-canonical CCT pair contacts must be prevented or displaced during TRiC assembly by kinetic or competitive barriers (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, CCT5 can interact with many other CCT subunits even in cells. Recombinant CCT4, CCT1, CCT2, and CCT6 can also homo-oligomerize in the absence of other subunits 48,49 . While we did detect CCT4-CCT4 and CCT2-CCT2 dimers after RP-HPLC, these dimers were not especially abundant in our native MS dissociation analyses.…”
Section: Discussionmentioning
confidence: 99%